Comparative Efficacy of Antidepressants for Symptoms Remission of Gastroesophageal Reflux: A Bayesian Network Meta-analysis of Randomized Controlled Trials - Si, Xiao-Bei; Huo, Lin-Yu; Bi, De-Ying; Lan, Yu; Zhang, Shuo (Turkish Journal of Gastroenterology, 2021)
Background: The present study aimed to compare and evaluate the efficacy of antidepressants in remission of esophageal reflux symptoms. Methods: A comprehensive literature review was performed including sources published on MEDLINE, EMBASE, the Cochrane Central Registry of Controlled Trials (Cochrane), Web of Science, China National Knowledge Infrastructure Database (CNKI), Chinese VIP Information Databases (VIP), Chinese Biology Medicine disc (CBM), and Wan-Fang databases for randomized controlled trials, published up to and including March 31, 2020. We analyzed relevant randomized, placebo-controlled trials reporting the effect of antidepressant therapy in relieving esophageal reflux symptoms. ADDIS 1.16.8 was used to perform the network meta-analysis. Furthermore, we performed a split analysis to test inconsistency, and rank probability was complemented for comparison among antidepressants. Results: A total of 10 randomized controlled trials (RCTs) examining the effects of antidepressants, selective 5-HT reabsorption inhibitor (SSRI), 5-HT 1A receptor agonist (5-HT1AA), tricyclic antidepressants (TCAs), and the complex of flupentixol-melitracen (FM) were included. Flupentixol-melitracen and SSRIs exhibited a significantly higher rate of remission than placebo. However, there was no statistically significant difference among different antidepressants compared. Rank probability showed that FM exhibited the highest probability of rank 1 compared with other antidepressants and placebo. Conclusion: This network meta-analysis of RCTs supported the use of FM and SSRIs as a potentially effective regimen for symptom remission of gastroesophageal reflux. Furthermore, according to our analysis, FM represents the most efficient antidepressant with highest probability of symptom remission.